2021
DOI: 10.1002/er.6817
|View full text |Cite
|
Sign up to set email alerts
|

A novel combined estimation method of online full‐parameter identification and adaptive unscented particle filter for Li ‐ion batteries SOC based on fractional‐order modeling

Abstract: Accurate estimation of the state of charge (SOC) of Li-ion battery can ensure the reliability of the storage system. A combined estimator of online fullparameter identification and adaptive unscented particle filter for Li-ion battery SOC based on an improved fractional-order model is proposed, which overcomes the shortcomings of the traditional SOC cumulative error and the difficulty of OCV acquisition. The proposed adaptive fractional unscented particle filter algorithm introduces fractional parameters as hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…141 The error can be less than 5% considering the extreme temperatures and dynamic conditions. 142 Considering OCV aging, 143 hysteresis, 98 noise adaptive, 144 etc. will be more effective in improving accuracy under 1%.…”
Section: Digital Management For Batterymentioning
confidence: 99%
“…141 The error can be less than 5% considering the extreme temperatures and dynamic conditions. 142 Considering OCV aging, 143 hysteresis, 98 noise adaptive, 144 etc. will be more effective in improving accuracy under 1%.…”
Section: Digital Management For Batterymentioning
confidence: 99%
“…Our previous work [35] has shown that the online identification algorithm is more suitable for model parameter identification under dynamic unknown conditions. Due to the nonlinear relationship between the order of the model and the output variables, the fixed value of the fractional order is obtained by the offline method, and the rest parameters are obtained by the online parameter identification method.…”
Section: Parameter Identificationmentioning
confidence: 99%
“…The results show that show that the SoC estimation accuracy can be significantly improved using the proposed method, with an estimation error in the range of 3% [131]. An adaptive unscented particle filter for lithium-ion battery SoC based on an improved fractional-order model is also proposed in [132]. The algorithm uses the fractional orders as hidden parameters, which reduces the number of particles and hence the complexity of the algorithm iteration.…”
Section: Applications Using Lithium-ion Batteriesmentioning
confidence: 99%